Degrees Kelvin : a tale of genius, invention, and tragedy - Lindley, David, 1956- (Joseph Henry Press, 2004)
Lindley presents a surprising and compelling portrait of William Thompson, a.k.a. Lord Kelvin, one of the most brilliant scientific minds of the 19th century.